Strategi Human Resource Departemen Dalam Meningkatkan Produktivitas Kerja Pegawai L’Avenue Office & Residence Jakarta Selatan - Marlena, Ena; Purwadhi, Purwadhi; Widjaja, Yani Restiani (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
Leadership is a key factor in the success of an organization, where an effective leader is able to inspire, motivate and direct the team to achieve common goals. Human Resources Management (HRM) has an important role as a central manager and provider of human resources for other departments, with the aim of managing labor relations effectively. Productivity is a fundamental component that a company must have to achieve its stated goals, where work productivity can be influenced by resources and the employees themselves. The Human Resources Department (HRD) has a vital role in implementing management and providing motivation to employees to increase productivity and quality of work in the company. The role of the Human Resources Department in improving employee performance is by providing training for all employees from previous years in order to increase productivity. Obstacles faced in increasing productivity include the existence of employees who have old thoughts/mindsets or find it difficult to keep up with developments in digital technology, there is still poor coordination between departments, overlapping work, lack of discipline, high employee turnover. and ways to overcome the obstacles faced include the commitment and efforts of the Human Resources Department in creating training programs for all employees which are carried out periodically, conducting regular product knowledge refreshments, selection in employee recruitment so that they match their educational background